(untitled) (Journal of Forensic Medicine & Toxicology, 2022)
In the current study, attenuated total reflectance- Fourier transform infrared (ATR-FTIR) spectroscopy has been utilized for the analysis of 24 different brands of hand sanitizers. Methanol was detected in few of the samples analyzed. Principal component analysis (PCA) was utilized on the obtained ATR-FTIR data to investigate and recognize the patterns of hand sanitizers on the PCA plot, and it further validated the presence of methanol in some samples. Finally, ethanol concentrations in hand sanitizers were determined by building a predictive model using different concentrations of standard ethanol. Three samples were found to have less than recommended ethanol concentration. The technique utilized in the present study has the ability to give results in quick time (within 5 minutes) and can be helpful for utilization in commercial regulations i.e., to quickly and reliably identify adulterants in hand sanitizers and also quantify ethanol content to see whether the concentration matches with that of the labeled concentration in the bottle